PENERAPAN FUZZY INFERENCE SYSTEM TIPE MAMDANI UNTUK MENENTUKAN JUMLAH PRODUKSI ROTI BERDASARKAN DATA JUMLAH PERMINTAAN DAN PERSEDIAAN (STUDI KASUS PABRIK CINDERELA BREAD HOUSE DI KOTA AMBON) - Sahulata, Elisabeth Rossemary Yunita; Wattimanela, H. J.; Noya Van Delsen, M. S. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Increased competitive competition in the economic development of each company engaged in the industry requires the company to win the competition by taking into account the inventory of goods to get the maximum profit. Therefore the planning of the number of products is very important to meet all existing requests. Writing and discussion in this study is the application of the Mamdani Fuzzy Inference System to determine the amount of production based on data on the amount of supply and demand at Cinderela Bread House Factory using the help of Matlab R2017a Software to determine the number of bakery products that must be produced. The application of Mamdani type Fuzzy logic in determining the amount of bread production based on the amount of supply and demand data can assist companies in making decisions with an accuracy value of 90.26633% and an error value of 9.77367%.